The use of the temporal muscle flap for the treatment of patients undergoing resection of ankylosis of the Temporomandibular Joint (TMJ): A systemic review (Research, Society and Development, 2024)
TMJ ankylosis is a fibrous/bone fusion between the condyle and the glenoid fossa, which leads to functional and aesthetic impairment. Resection is usually the treatment of choice, but it suggests the need to re-establish a new joint structure. Temporal muscle interposition is described as a viable and less expensive technique compared to joint prosthesis. The aim of this article was to carry out research into TMJ ankylosis by means of a literature review, which included scientific articles indexed in databases such as Google Scholar, SciELO and PubMed, many of which showed that temporal muscle interposition is an excellent alternative for reconstructing the joint structure and preventing its recurrence. Our aim is to provide a review of the articles published in the literature in order to ensure a scientific basis for the use of the temporal muscle flap as an alternative for patients who will undergo resection of joint ankylosis and do not have greater resources for the installation of TMJ prostheses. Finally, the use of the temporal muscle flap proved to be an alternative for cases of resection of ankylosis of the temporomandibular joint. It is easy to perform, does not require an additional surgical site for removal of material and does not require greater financial and technological resources to carry out the technique.